2010 IEEE International High Level Design Validation and Test Workshop (HLDVT) 2010
DOI: 10.1109/hldvt.2010.5496659
|View full text |Cite
|
Sign up to set email alerts
|

Coverage metrics for verification of concurrent SystemC designs using mutation testing

Abstract: Abstract-Design verification has grown to dominate the cost of electronic system design; however, designs continue to be released with latent bugs. A verification test suite developed for a sequential program is not adequate for a concurrent program. A major problem with design verification of concurrent systems is the lack of good coverage metrics. Coverage metrics are heuristic measures of the exhaustiveness of a test suite. High coverage, in general, implies fewer bugs. SystemC is the most popular concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…However, by effectively ignoring redundant faults (that is, not treating them as coverage holes), coverage discounting enables the end user to employ more subtle fault models without the overhead of redundant fault identification. 1) Mutation Analysis: As previously mentioned, mutation analysis is a well established software testing technique [3] which has recently been adopted for hardware validation [4]- [7]. An overview of mutation analysis research can be found in [15].…”
Section: B Fault Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by effectively ignoring redundant faults (that is, not treating them as coverage holes), coverage discounting enables the end user to employ more subtle fault models without the overhead of redundant fault identification. 1) Mutation Analysis: As previously mentioned, mutation analysis is a well established software testing technique [3] which has recently been adopted for hardware validation [4]- [7]. An overview of mutation analysis research can be found in [15].…”
Section: B Fault Insertionmentioning
confidence: 99%
“…Fault insertion, such as mutation analysis [3], has been proposed to evaluate the tests' ability to detect errors, originally for software testing. While this technique has been adapted to hardware validation tools [4]- [7], the information it provides is of limited utility: it does not expose test holes with a specific functional meaning (as coverage metrics do). The holes provided by fault insertion are undetected faults, but these faults are neither guaranteed detectable at all nor are they necessarily functionally meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…With simulation still as the main way of HDL verification, there is a fundamental question: how can we comprehensively measure and control the quality of these simulation-based verification processes? In this context, mutation testing [7,8] by the mutation-based fault injection and analysis has been studied and deemed as an effective and significant coverage metric for VHDL, Verilog, and SystemC simulations [20,3,1,2]. Depending on the language constructs of each HDL, a single design error, or a so-called mutation fault is deliberately introduced into the design, such as replacing an and operator by an or:…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use a previously developed mutation library for MCAPI standard that targets message passing communication constructs. There is also several work in the literature on using mutation testing for Java, C, and SystemC [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%